We need to teach human rights in medical schools - Weishut, Daniel; Aitchison, Lucy; Steiner-Birmanns, Bettina (Torture Journal, 2021)
There are protocols of the questioning of a young military physician in the Israeli Defense Forces, who performed a vaginal examination on a Palestinian woman under arrest, against the latter’s expressed will and without a medical indication. In support of the WMA guidelines on including human rights courses in medical schools, we call on medical schools to integrate a human rights perspective and introduce sufficient material on human rights, prisoners’ rights and medical ethics to help physicians like her make the right decisions in challenging situations such as the one described.